ANALISIS PENGARUH DIVERSIFIKASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA UKM GULA KELAPA - Danis Imam Bachtiar (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
In the discussion of this study, the problem is how much influence the product and pricediversification of purchasing decisions in SMEs Palm Sugar in Purworejo District. While thefocus of the problem is how much product diversification influences purchasing decisions,how much the price affects purchasing decisions as well as whether product and pricediversification simultaneously affect purchasing decisions in SMEs Palm Sugar in PurworejoDistrict. Discussion of this research is a field research with quantitative descriptive approachmethod that describes the effect of product and price diversification to purchasing decision inSME Gula Kelapa in Purworejo Regency. Techniques of collecting data obtained fromobservations and questionnaires distributed To Consumers Coconut Sugar in PurworejoDistrict. The result of data processing is product diversification has a positive effect onpurchasing decision, it is proved by titung 2,900 bigger than ttable equal to 1,661. Price hasa positive influence on purchasing decisions, this is evidenced by t count of 5.680 is greaterthan the t table of 1.661. While the results of the test together product and pricediversification affect the purchase decision of 78.77. The result of determination coefficient isproduct diversification and price can explain purchase decision of 65,5%.Keywords: Product diversification, price and purchase